KEMAMPUAN GURU DALAM MEMBUAT SOAL UJIAN SEMESTER MENGGUNAKAN IN HOUSE TRAINING (IHT) DI SDN 025 HARAPAN JAYA - Warsudi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to see the teachers' ability in designing semester tests. A good learning process enables the main learning objectives to be achieved adequately. The success of the teaching and learning process is seen from the ability to solve the problems, and students feel comfortable with the ongoing learning. A suitable method makes students feel interested in what they are learning. In this case, to see student learning outcomes, teachers must also have the ability to make questions or semester exam tests; this is done to evaluate how students' learning outcomes are achieved. This study was School Action Research (SAR) using a research design model of Kemmis and Mc. Taggart. The research was conducted at SD Negeri 025 Harapan Jaya, with the subjects of the study being the seven teachers there. The study, conducted in two cycles, revealed that the teachers' ability or understanding to design semester tests increased. It was found that the percentage in the first cycle was 30%, while the percentage in the second cycle was 70%. This study results reflected the teachers' ability to make and understand the rules of the semester tests according to the subjects they taught.